Katecheza i liturgia według katechez Cyryla Jerozolimskiego (+387) - Witko, Krzysztof (Studia Pastoralne, 2026)
Since its beginnings Christianity has shown a close and direct connection with liturgy and catechesis. Cyril of Jerusalem is a privileged witness to their mutual relation in the ancient Church. The paper seeks to show the liturgical and theological depth of his catechetical heritage in four points: Cyril of Jerusalem – witness to the baptismal catechesis of the fourth century; three dimensions of the baptismal catechesis of Cyril of Jerusalem (dogmatic, moral and sacramental one); typological interpretation of the Scriptures, mystagogical catechesis of Cyril of Jerusalem and their relation with liturgy. In the conclusion we draw readers’ attention to a sacramental perspective of the Christian vision of the history of Catechesis of Cyril of Jerusalem that remains valid for contemporary Christians.